Globalization and Migratory Processes in the Socio-reli-gious, Economic and Political Context of the Malay Muslims of Malaysia - Cheong, John (Transformation, 2008)
Globalization in Malaysia has introduced the Malay Muslim population to new ethno- religious dynamics at the urban-to-urban level internationally and rural-to-urban sphere nationally. At the international level, Malay Muslims who studied abroad have returned with alternate conceptions of Islam at odds with the local version as well as fostered transnational links to outsiders that later facilitated their religious influence locally. At the national level, Malay Muslim migration to an urban economy opened to global capitalism have produced reactionary discourses and attitudes by conservative Muslims desirous of countering the excesses of this economic reality. Implications for a Christian holistic transformation in light of these dynamics are proposed.